In Defence of Guerrillas (Diametros, 2010)
This article examines the moral issues of guerrilla, and counter-guerrilla, warfare. Just war theorists who have studied the phenomenon tend to claim that the guerrilla tactic of wearing civilian clothes and hiding among the civilian population is rather difficult, if at all, to reconcile with the ius in bello principle of discrimination (the principle according to which combatants have to distinguish between combatants and non-combatants and may only target the former “directly”). I argue that this ever-repeated assessment is profoundly confused. I also argue, conversely, against the claim that this guerrilla tactic makes it somehow easier for the counter-insurgents to comply with the principle of discrimination, thereby easily allowing them to resort to tactics like area bombardment. Finally, I demonstrate that, contrary to common opinion, guerrilla war does not face greater difficulties in complying with ius ad bellum requirements than conventional or counter-insurgency war does.